IMPROVEMENT OF SYSTEMS FOR MONITORING AND CONTROLLING THE PROCESS OF FREEZING PRODUCTS IN REFRIGERATING CHAMBERS OF INDUSTRIAL REFRIGERATORS - KHOROLSKY, VALENTYN; KORENETS, YURII; PETRUSHYNA YULІYA; RASCHEKHMAROV, IVAN (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article proposes a set of theoretical and practical attributes associated with design decisions regarding the processes of freezing meat products in refrigerators with a large load capacity of industrial refrigerators. A system of intelligent sensors has been developed to control the parameters of the geometry of the carcass of cattle meat and signs of the state of the evaporators of the refrigeration chamber and the refrigeration supply system of an industrial refrigerator. An automatic recognition system has been developed that works in real time and determines: geometric parameters of local and integral sections of the carcass in the form of a plane, radii, length, width, number of contour inflection points, geometric center of image elements; humidity settings. This system constantly analyzes the space of sections of the refrigerating chamber. An intelligent system for neurocontrol of the refrigeration supply of a refrigerating chamber is proposed, in which two video cameras and matrix sensors with piezoelectric elements for assessing the shape of a cattle carcass are mounted; it has been proved that the expert ink image bank allows using reference methods of comparative analysis. Thanks to the interface with information support subsystems, the system provides the operator-technologist with video information and automatically affects the intelligent actuators of compressors, fans, condensers. A system for neuro-fuzzy control of the evaporator freezing process has been developed, which provides for an expert system, a recognition algorithm, an expert image bank of an evaporator with a snow coat and an intelligent mechanism for the impact of ultrasonic vibrations on the surface of a cooling device. A generalized algorithm for the operation of refrigeration control systems for the refrigerating chamber of an industrial refrigerator and a method for its use are presented.